1992
DOI: 10.1210/en.130.1.421
|View full text |Cite
|
Sign up to set email alerts
|

Immunodetection of estrogen receptors in fetal and neonatal male mouse reproductive tracts

Abstract: Immunodetection methods were used to detect estrogen receptors (ER) in male reproductive tracts on fetal days 13, 15, and 17 and on the day of birth. Immunocytochemistry revealed that most of the cells of the gonad and associated Wolffian duct stained for ER on fetal day 13. During the next 6 days, ER distribution changed, and by the day of birth, ERs were observed only in epithelial cells of the epididymis (derived from the Wolffian duct) and in a portion of cells from the testis. Immunoblots confirmed that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 0 publications
3
30
0
Order By: Relevance
“…Uterine stromal cells stained for ER were observed at all ages examined, but staining appeared to decrease with age in the control animals and with DES treatment. Similar results have been reported in male (18) and female (19) mouse reproductive tract tissues following neonatal exposure to DES (20). Additional information on the role of ER in embryonic tissues has been described by Gorski and Hou (21).…”
Section: Murine Model Of Developmental Exposure To Diethylstilbestrolsupporting
confidence: 86%
“…Uterine stromal cells stained for ER were observed at all ages examined, but staining appeared to decrease with age in the control animals and with DES treatment. Similar results have been reported in male (18) and female (19) mouse reproductive tract tissues following neonatal exposure to DES (20). Additional information on the role of ER in embryonic tissues has been described by Gorski and Hou (21).…”
Section: Murine Model Of Developmental Exposure To Diethylstilbestrolsupporting
confidence: 86%
“…It differs from other histological investigations of oestrogen receptor expression in mice during this period (Stumpf et al, 1980;Holderegger and Keefer, 1986;Cooke et al, 1991;Greco et al, 1991Greco et al, , 1992 in the following ways. First, the use of oestrogen receptor-specific antibodies rather than radiolabelled ligands (that is, […”
Section: Discussionmentioning
confidence: 70%
“…However, these studies have limitations in histological interpretation as a result of the use of either autoradiography (Stumpf et al, 1980;Schleicher et al, 1984;Holderegger and Keefer, 1986;Cooke et al, 1991) or frozen sections (Greco et al, 1991(Greco et al, , 1992. Furthermore, these studies do not discriminate between ER-α and ER-β.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies from this laboratory, Greco et al. (16)(17)(18) showed that ER is present in both male and female mice from gestational day 10 and later, with definite evidence of ER being present in reproductive tissues at gestational day 1 or later. This includes the gonads (Figure 3) (18) Currently there is a great deal of interest in environmental estrogens that originate from sources such as chemical processing or foods that contain mycotoxins or phytoestrogens.…”
Section: Environmental Health Perspectives Embryonic Estrogen Receptorsmentioning
confidence: 92%